2021
DOI: 10.4028/www.scientific.net/kem.902.101
|View full text |Cite
|
Sign up to set email alerts
|

A Study of an Effect on Moisture from 3D Printer Filament Drying Processes

Abstract: This study investigated characteristics of moisture desorption for polylactic acid (PLA) filaments. The filaments tend to absorb moisture from humid air, led to moisten filaments. The absorption of even small amounts of moisture by filaments during storage and/or 3D printing, degraded the quality of final parts, and therefore, caused manufacturing problems. In this work, the filaments were subjected to humid conditions to achieve various moisture concentrations (0.75, 1.3 and 1.87 wt.%). Warm air-drying proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…In addition, a study by Löbmann and colleagues [33] found that both convection and microwave-induced radiation play a crucial role in promoting in situ drug amorphization, which can influence their bioavailability and clinical effectiveness. Some of these studies have investigated different drying methods, with the expectation that the heating mechanism underlying microwave drying might be more beneficial to the performance and quality of the products [33][34][35][36]. However, the work published to date has focused on the application of the drying step only to intermediate products obtained by HME.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study by Löbmann and colleagues [33] found that both convection and microwave-induced radiation play a crucial role in promoting in situ drug amorphization, which can influence their bioavailability and clinical effectiveness. Some of these studies have investigated different drying methods, with the expectation that the heating mechanism underlying microwave drying might be more beneficial to the performance and quality of the products [33][34][35][36]. However, the work published to date has focused on the application of the drying step only to intermediate products obtained by HME.…”
Section: Introductionmentioning
confidence: 99%